2016
DOI: 10.1039/c6tc03989h
|View full text |Cite
|
Sign up to set email alerts
|

Role of rare earth ions in the magnetic, magnetocaloric and magnetoelectric properties of RCrO3 (R = Dy, Nd, Tb, Er) crystals

Abstract: H-induced stair-like metamagnetic transitions, large magnetocaloric and magnetoelectric effects related to the 4f electrons of rare-earth ions were revealed in chromite crystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…The similar scenario occurs due to the electric field poling of RCrO3, which destroys antiferroelectric configurations and leads to the concomitant reorientation of magnetic moments coupled with the rare earth ions electric dipoles. The possible coupling of the order parameters couplings (DOP-FOP-MOP) are revealed by the classification of distortion modes, electric-dipole and magnetic moments of R 3+ ions; magnetic moments of Cr 3+ ions on the irreducible representations of the RCrO3 symmetry group (D2h 16 ) allows. Thus, we determine the possible magnetic and ferroelectric configurations, their transformations during spin reorientation phase transitions accompanied with the ferroelectric reversal and compare our findings with results of experimental measurements on RCrO3 (R=Sm, Tm, Tb, Gd, Er, Lu) [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The similar scenario occurs due to the electric field poling of RCrO3, which destroys antiferroelectric configurations and leads to the concomitant reorientation of magnetic moments coupled with the rare earth ions electric dipoles. The possible coupling of the order parameters couplings (DOP-FOP-MOP) are revealed by the classification of distortion modes, electric-dipole and magnetic moments of R 3+ ions; magnetic moments of Cr 3+ ions on the irreducible representations of the RCrO3 symmetry group (D2h 16 ) allows. Thus, we determine the possible magnetic and ferroelectric configurations, their transformations during spin reorientation phase transitions accompanied with the ferroelectric reversal and compare our findings with results of experimental measurements on RCrO3 (R=Sm, Tm, Tb, Gd, Er, Lu) [6].…”
Section: Discussionmentioning
confidence: 99%
“…Crystal structure and magnetic properties of rare earth orthochromites RCrO3 studied since 1960s [10 -12] are well established. They belong to the space symmetry group Pbnm (D2h 16 ). Neutron diffraction measurements showed that the Cr 3+ ions order antiferromagnetically in Gtype magnetic configurations with weak ferromagnetic component…”
Section: Introductionmentioning
confidence: 99%
“…Various other striking properties have been observed in related orthochromites and orthoferrites including magnetocaloric effects [9][10][11][12], magnetization reversal [13,14], negative thermal expansion [14], and diverse magnetoelectric effects [11,[15][16][17]. All these properties are highly dependent on magnetic interactions between the involved cations [18].…”
Section: Introductionmentioning
confidence: 99%
“…The Néel temperature can be improved without affecting the saturation magnetization when Mn is substituted with Cr [11,12]. RCrO 3 (R = La, Pr, Sm, Nd, Gd, Tb, Ho, Dy, Er, Tm, Lu) compounds have shown potential multiferroic properties mostly due to the exchange striction between the R and Cr moments [13][14][15][16][17][18][19][20][21]. The NdCrO 3 magnetization curve differs significantly from those typically found in the rare-earth orthochromites [22].…”
Section: Introductionmentioning
confidence: 99%
“…Shanker et al [21] reported that NdCrO 3 is a relaxor ferroelectric (500 K at 1 MHz). Yin et al [20] reported a dielectric anomaly in the vicinity of the Nd 3+ spins ordering the temperature of the NdCrO 3 , but the nature of the anomaly was not clear.…”
Section: Introductionmentioning
confidence: 99%